Transformasi Digital Pelayanan Publik Kota Batu: Menuju Tata Kelola Pemerintahan yang Adaptif dan Responsif - Laila Rahmawanti Ringtyas; Hayat; Suyeno (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2026)
Digital transformation has become a strategic necessity in modern public administration, not merely as a technological innovation but also as an instrument of governance reform. Batu City, with its tourism- and agriculture-based economy, faces diverse and complex demands for public services. The local government has responded by developing several applications, such as Lapor Batu, Among Batu, e-Puskesmas, and Batu Among Tani Teknologi (BATT). Nevertheless, the implementation of these digital services remains constrained by limited ICT infrastructure, low levels of digital literacy, weak inter-agency system integration, and inadequate bureaucratic capacity. This study aims to describe the implementation of digital transformation in Batu City and to analyze its contribution to the realization of adaptive and responsive governance. The research employs a qualitative descriptive approach using literature review and document analysis, with data drawn from government policy documents, SPBE reports, scholarly publications, and national surveys. The findings reveal that digital innovations in Batu City have expanded into the areas of complaints management, licensing, healthcare, education, and cultural services, yet they remain at an early stage with limited effectiveness. The conclusion highlights that digital transformation in Batu City holds potential as a foundation for adaptive and responsive governance, but requires stronger system integration, institutional capacity, and citizen participation to achieve inclusive and sustainable benefits.